2021
DOI: 10.3390/ijms22094307
|View full text |Cite
|
Sign up to set email alerts
|

The Calcium/Calmodulin-Dependent Kinases II and IV as Therapeutic Targets in Neurodegenerative and Neuropsychiatric Disorders

Abstract: CaMKII and CaMKIV are calcium/calmodulin-dependent kinases playing a rudimentary role in many regulatory processes in the organism. These kinases attract increasing interest due to their involvement primarily in memory and plasticity and various cellular functions. Although CaMKII and CaMKIV are mostly recognized as the important cogs in a memory machine, little is known about their effect on mood and role in neuropsychiatric diseases etiology. Here, we aimed to review the structure and functions of CaMKII and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(19 citation statements)
references
References 241 publications
(377 reference statements)
0
19
0
Order By: Relevance
“…A new in silico study revealed a CaMKII motif in the S antigen of SARS-CoV-2, suggesting that this virus may disrupt cognition directly ( Wenzhong and Hualan, 2021 ) ( Figure 3 and Table 2 ). Interestingly, CaMKII inhibitors were reported to possess antiviral and antipsychotic properties, further emphasizing the role of Ca2+ signaling in these pathologies ( Sałaciak et al., 2021 ). Ca2+ and tubulin also participates in the functioning of the immune synapse, therefore viral exploitation of this protein may disrupt host immunity ( Hui and Upadhyaya, 2017 ; Sferra et al., 2020 ).…”
Section: Cell-cell Fusion the Molecular Actorsmentioning
confidence: 99%
“…A new in silico study revealed a CaMKII motif in the S antigen of SARS-CoV-2, suggesting that this virus may disrupt cognition directly ( Wenzhong and Hualan, 2021 ) ( Figure 3 and Table 2 ). Interestingly, CaMKII inhibitors were reported to possess antiviral and antipsychotic properties, further emphasizing the role of Ca2+ signaling in these pathologies ( Sałaciak et al., 2021 ). Ca2+ and tubulin also participates in the functioning of the immune synapse, therefore viral exploitation of this protein may disrupt host immunity ( Hui and Upadhyaya, 2017 ; Sferra et al., 2020 ).…”
Section: Cell-cell Fusion the Molecular Actorsmentioning
confidence: 99%
“…This protein isoform to is known to be mainly expressed in the brain neurons and it is well established that its abnormal functioning is linked to the pathophysiology of depression. So far most studies associated the decrease in CaMKII alpha levels to the depressive like phenotype in animal models and highlighted the role of antidepressants to increase this protein expression ( Sałaciak et al, 2021 ). In their review paper Salaciak and colleagues discussed the effect of CaMKII in antidepressant-like effect installation mentioning that this activity requires the activation of both CaMKIIα and CaMIV together with the inactivation of CaMKIIβ.…”
Section: Discussionmentioning
confidence: 99%
“…Signaling molecules downstream to NMDARs, like CaMKII, can also be targeted to restore Ca 2+ and glutamate homeostasis at synapses ( Vest et al, 2010 ). Likewise, CaMKII has been exploited as a potential drug target in neuropsychiatric and neurodegenerative diseases ( Sałaciak et al, 2021 ).…”
Section: Ca 2+ /Calmodulin-dependent Protein Kinas...mentioning
confidence: 99%